Relação Estrutura-Atividade de Fragmentos da Leptina - Martins, Marta Natividade Crizol [UNIFESP] (2008)
The protein hormone produced by the ob-gene and denominated leptin, a product originating from adipose tissue, circulates in the plasma and affects the energy balance by interacting with the hypothalamus. Leptin plays an important role in the regulation of a variety of physiological functions, including food intake, body temperature and body weight maintenance. Total absence or resistance to leptin causes morbid obesity, diabetes and hypogonadism. The tertiary structure of the leptin molecule reveals the existence of a fourhelix bundle that is characteristic of the short-helix cytokines. To identify regions of the leptin molecule responsible for its bioactivity, we have synthesized six peptides based on the protein three-dimensional structure. Our results indicated that the fragments AchLEP92- 115-NH2 (IV) and Ac-[Ser117]-hLEP116-140-NH2 (V) were recognized by leptin receptor present in hp-75 cells, in agreement with the obtained by other authors, validating that this region of the molecule contain the functional epitope of the leptin molecule. In the present study, a new series of peptides encompassing the region of fragments IV and V of leptin were synthesized, and their effects on body weight and food intake were assessed when administered into the lateral cerebroventricle of normal rats. Peptides were synthesized by the solid phase methodology, purified by RP-HPLC and characterized by LC/ESI-MS. We also performed a conformational study of the peptides by circular dichroism in order to correlate the biological activity and secondary structure of the leptin fragments. Out off the new series of compounds, the best results were obtained with the fragment Ac-hLEP110-119-NH2 (VI) which showed to be more active than leptin and equipotent to [D-Leu4]-OB3 the most active leptin fragment described in the literature so far. Although the peptide fragments design needs refinement, this kind of approach may offer the basis for the development of leptin-related compounds with potential application in human obesity or veterinary medicine.